Philosophy in Educational Development and Improving Critical Thinking Skills: A Scientific and Reflective Approach - Audra Ayu Bagascary; Ahmad Syukri; Badarussyamsi (International Journal of Education, Language, and Social Science, 2025)
Contemporary education faces increasingly complex challenges, especially in forming students who are not only academically intelligent, but also able to think critically and positively in the face of information that is full of bias and uncertainty. This article aims to explore the role of philosophy in the development of contemporary education, with a focus on how philosophy can form students who have a positive and critical framework of thinking. This study uses a library research approach by analyzing relevant literature on philosophy and education. The sources used include books, journal articles, and related studies that discuss the relationship between philosophy and critical education. The results of the study show that philosophy provides a strong theoretical basis for developing more reflective and critical education. In addition, the application of philosophical principles in education can produce individuals who are more independent, critical, and reflective in facing various dynamics of life.